Оцінка сучасного стану та перспектив розвитку туристичної інфраструктури в окремих об’єднаних територіальних громадах Волинської області - Чир, Надія Вікторівна; Качаровський, Роман Євгенович; Chyr, Nadiia V.; Kacharovskyi, Roman Ye. (Тернопільський національний педагогічний університет імені Володимира Гнатюка, 2017)
Здійснено комплексну оцінку сучасного стану та перспектив розвитку туристської інфраструктури окремих об’єднаних територіальних громад Волинської області (на прикладі Устилузької та Зимнівської ОТГ Володимир-Волинського району) за окремими підсистемами: заклади розміщення, заклади харчування, заклади дозвілля та побутового обслуговування, транспортна інфраструктура, звʼязок та інформаційне забезпечення. Визначено основні проблеми структурних елементів туристичної інфраструктури, запропоновано можливі шляхи їх вирішення.

The integrated assessment of the current state and the prospects of development of the tourist infrastructure in the united territorial communities of Volhyn region (on the example of Ustylug UTC and Zimnenska UTC) has conducted. This assessment has implemented of individual subsystems: accommodation establishments, food establishments, leisure facilities, consumer services establishments, transport infrastructure, communication and information services. The main problems of the constituents of the tourist infrastructure have been determined. Possible ways of the solution of these problems are suggested. The united territorial communities have a significant tourist and recreational resources for the organization of tourist activities. The weakest element of the tourist potential of the territory is the tourist infrastructure. The results of the research give an opportunity to state that the coefficient of provision of the accommodation establishments is rather low compared with the average of the region and become 0,002 un./km². The coefficient of provision of the food establishments is higher and become about 0,03 un./km².The subsystem "leisure facilities" is the weakest link in the tourist infrastructure on the explored territories. We also mark a positive aspect of the cross-border position of the territory and the sufficiently high level of development the transport infrastructure. The main problems of the united territorial communities are: lack of the infrastructural arrangement and information support of the most attractive objects of cultural heritage and the nature reserved fund, which are the most popular among the tourists; the low degree of the rural green tourism development; lack of information about the tourist-recreational opportunities of the territory, the absence of the required number of placements, low competitiveness facilities of the restaurant business and the entertainment industry, bad function of the Internet in rural areas. As a factor of optimization and development of the tourist infrastructure on the researched united territorial communities should be proposed the creation of the "thematic villages". The experience of there creation was being successfully implemented in the neighboring Poland.
The assessment of the current state and the prospects of development of the tourist infrastructure in the united territorial communities of Volhyn region
Keywords: туристична інфраструктура; об’єднана територіальна громада; Устилузька ОТГ; Зимненська ОТГ; Володимир-Волинський район; Волинська область; tourism; tourist infrastructure; united territorial community; Ustylug UTC; Zimnenska UTC